PERUBAHAN RUANG TERBUKA HIJAU KECAMATAN KOTO TANGAH PERIODE TAHUN 2018-2022 - Hadi Wiryanto; Dwi Arini; Fajrin; Ilham Armi (ADMIN: Jurnal Administrasi Negara, 2024)
Koto Tangah is one of the sub-districts in Indonesia, specifically in the city of Padang, West Sumatra province. Koto Tangah sub-district has an area of 232.25 km2 or around 33.42 percent of the total area of Padang City. Along with the development of Padang City in the last five years to be precise in 2018-2022. There are changes in Green Open Space that have occurred in the Koto Tangah District area. In this research, to determine changes in Green Open Space in Koto Tangah District, we use Geographic Information Systems (GIS) and Remote Sensing to detect changes in Green Open Space using Google Earth imagery in 2018. -2022 and to find out the pattern of green open space distribution using the nearest neighbor method or nearest neighbor analysis from the results of calculating the percentage (%) of the total area of Green Open Space in Koto Tangah District from 2018 to 2022, the result is that there is a decrease in the number of green open spaces available by 1, 1% with the total green open space area in 2018 amounting to 16,203, 3333 ha (73.5%) and the total green open space area in 2022 amounting to 15,870.92 ha (72.4%) from the area of Koto Tangah sub-district with the distribution pattern of the nearest green open space, then It is known that the distribution pattern of green open spaces is clustered. Based on Law No. 26 of 2007 concerning Spatial Planning, the proportion of green open spaces is at least 30 (thirty) percent of the city area. The total availability of green open spaces in Koto Tangah sub-district from 2018 to 2022 is sufficient.